Acid catalyzed one-pot approach towards the synthesis of curcuminoid systems: unsymmetrical diarylidene cycloalkanones, exploration of their single crystals, optical and nonlinear optical properties. Issue 7 (2nd February 2023) - Ali, Akbar; Din, Zia Ud; Ibrahim, Muhammad; Ashfaq, Muhammad; Muhammad, Shabbir; Gull, Dania; Tahir, Muhammad Nawaz; Rodrigues-Filho, Edson; Al-Sehemi, Abdullah G.; Suleman, Muhammad
Abstract : In the present study crystalline unsymmetrical diarylidene ketone derivatives BNTP and BDBC have been prepared by two sequential acid catalyzed aldol condensation reactions in a one pot manner. Abstract : In the present study crystalline unsymmetrical diarylidene ketone derivatives BNTP and BDBC have been prepared by two sequential acid catalyzed aldol condensation reactions in a one pot manner. The crystal structures of both compounds were confirmed by single crystal X-ray diffraction analysis which revealed the presence of H-bonding interactions of type C–H⋯O, along with weak C–H⋯π and weak π⋯π stacking interactions that are involved in the crystal stabilization of both organic compounds. Hirshfeld surface analysis is carried out for the broad investigation of the intermolecular interactions in both compounds. The quantum chemical investigation was performed on the optimized molecular geometries of BNTP and BDBC to calculate optical and nonlinear optical (NLO) properties. The density functional theory (DFT) study showed that the third-order NLO polarizabilities of compounds BNTP and BDBC are found to be 226.45 × 10 −36 esu and 238.72 × 10 −36 esu, respectively, which indicates noticeable good NLO response properties. Additionally, the BNTP and BDBC molecules also showed the HOMO–LUMO orbital gaps of 5.96 eV and 6.06 eV, respectively. Furthermore, the computation of UV-visible spectra of the titled compounds indicated a limited and/or no absorption above the 400 nm region, directing a good transparency and NLO property trade-off for both synthesized compounds that may play a significant contribution in the future for optoelectronic technologies.